Genetic alterations in LEP and ADIPOQ genes and risk for breast cancer: a meta-analysis - Peng, Wei-zhao; Liu, Xin; Li, Chao-feng; Zhao, Jin (Frontiers in Oncology, 2023)
Breast cancer has a strong genetic predisposition, and its genetic architecture is not fully understood thus far. In this study, we aimed to perform a meta-analysis to evaluate the association of genetic alterations in LEP and ADIPOQ genes, as well as their receptor-encoded genes with risk for breast cancer. Only published studies conducted in humans and written in English were identified by searching PubMed, SCOPUS, CINAHIL and Embase from their inception to October 2022. Eligibility assessment and data collection were completed independently by two researchers. Statistical analyses were done using the STATA software. After literature search, 33 publications were eligible for inclusion. Overall, LEP gene rs7799039-G allele (odds ratio [OR]: 0.78, 95% confidence interval [CI]: 0.62 to 0.98) and ADIPOQ gene rs1501299-T allele (OR: 1.41, 95% CI: 1.06 to 1.88) were associated with the significant risk of breast cancer. In subgroup analyses, differences in menopausal status, obesity, race, study design, diagnosis of breast cancer, genotyping method and sample size might account for the divergent observations of individual studies. Circulating leptin levels were comparable across genotypes of LEP gene rs7799039, as well as that of LEPR gene rs1137101 (P>0.05). Begg’s funnel plots seemed symmetrical, with the exception of LEPR gene rs1137100 and ADIPOQ gene rs1501299. Taken together, we found, in this meta-analysis, that LEP gene rs7799039 and ADIPOQ gene rs1501299 were two promising candidate loci in predisposition to breast cancer risk.